Influence of material properties on scratch-healing performance of polyacrylate-graft-polyurethane network that undergo thermally reversible crosslinking. (16th October 2017) - Kim, So Young; Lee, Tae Hee; Park, Young Il; Nam, Joon Hyun; Noh, Seung Man; Cheong, In Woo; Kim, Jin Chul
Abstract: Scratch-healing poly (methyl methacrylate)- co -[poly (methyl metharyleate)- graft -(oligo-caprolactone)] urethane networks containing a Diels Alder (DA) adduct unit (GCPNp-DAs) were successfully synthesized and shown to be capable of undergoing thermally reversible crosslinking. The synthesized polymers were coated on steel substrates to investigate the influence of their material properties on their scratch-healing performance. The reversible formation of crosslinked and de-crosslinked structures of the GCPNp-DAs at DA and retro-DA (rDA) reaction temperatures was demonstrated using FT-IR spectroscopy, differential scanning calorimetry (DSC), oscillatory rheology, and nanoindentation. The scratch-resistance and healing performances of the GCPNp-DA coatings were evaluated quantitatively using a scratch test machine equipped with an optical microscope (OM) and an atomic force microscope (AFM). These results were found to be greatly influenced by the material properties of the coatings such as the elastic modulus, indentation hardness ( H IT ), crosslinking density ( v c ), and thermal transition temperature as well as by whether the deforming load that produced the scratches was increased in a progressive (gradual) or step-wise manner. Graphical abstract: Highlights: Scratch-healing polyacrylate- graft -polyurethane networks were prepared. Reversible formation of crosslinked and de-crosslinked structures were demonstrated. Scratch-healing performances of the polymer networks were quantitatively analyzed. Effects of materials properties on the scratch-healing performances were investigated.